Intelligent Stereo Garage Based on UV Sampling Algorithm - Dan Wang; Xi Chen; Huanhuan Xu; Zhenhao Chen; Jinfeng Chen (IJRDO - Journal of Mechanical And Civil Engineering, 2020)
Nowadays motor vehicle ownership is huge and continues to increase, and the demand for parking spaces has become a major social problem, which also involves the use of contemporary land resources. The traditional parking lot limits the effective use of land resources, and parking difficult problem causes a lot of troubles to people's life, government management and urban construction. Therefore, this paper designs a stereo garage system based on UV sampling algorithm for motor vehicles in old community public space. Using pre-set program, vehicles are accessed through electronic control machinery and other means to realize intelligent parking. It is not only improves the utilization rate of land resources, but also solves parking difficult problem.